Methylene blue-containing liposomes as new photodynamic anti-bacterial agents. Issue 15 (29th March 2017) - Boccalini, Giulia; Conti, Luca; Montis, Costanza; Bani, Daniele; Bencini, Andrea; Berti, Debora; Giorgi, Claudia; Mengoni, Alessio; Valtancoli, Barbara
Abstract : Novel cationic liposomes containing the photo-activatable drug methylene blue (MB) strongly enhance the antibacterial activity of MB towards Gram-negative bacteria and improve biofilm penetration. Abstract : Methylene blue (MB) can be employed as a photo-activatable antimicrobial drug in photodynamic therapy (PDT) due to its ability to release oxygen free radicals upon photo-activation. However, its poor ability to penetrate bacterial cell walls and bacterial biofilms limits its antimicrobial activity. To overcome these limitations, we propose some formulations of MB based on different cationic liposomes. The liposome–MB systems were characterized using dynamic light scattering (DLS), zeta potential analysis and UV-visible spectroscopy. Their ability to penetrate inside the cytoplasm of E. coli, taken as a bacterial model for Gram-negative strains, was investigated through laser scanning confocal microscopy (CLSM) and compared to the penetration of naked MB. Then, MB-loaded liposomes were photo-activated and their antimicrobial activity was tested against E. coli, showing a strong improvement with respect to MB solutions. The liposomal formulations dramatically enhance MB penetration in bacterial biofilms and reduce the inflammatory response due to lipopolysaccharide exposure in mammalian cells. The observed antimicrobial and anti-inflammatory efficacies show a clear correlation with some structural features of the carriers, namely the size and the surface charge density. Overall, these results provide fundamental knowledge that enables the design of novel efficient PDT treatments, which potentially overcome the rising incidence of antibiotic resistance of bacterial strains.